2008
DOI: 10.1677/joe-07-0542
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-4 interacts with activin and GnRH to modulate gonadotrophin secretion in LβT2 gonadotrophs

Abstract: We have shown previously that, in sheep primary pituitary cells, bone morphogenetic proteins (BMP)-4 inhibits FSHβ mRNA expression and FSH release. In contrast, in mouse LβT2 gonadotrophs, others have shown a stimulatory effect of BMPs on basal or activin-stimulated FSHβ promoter-driven transcription. As a species comparison with our previous results, we used LβT2 cells to investigate the effects of BMP-4 on gonadotrophin mRNA and secretion modulated by activin and GnRH. BMP-4 alone had no effect on FSH produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
1
37
0
2
Order By: Relevance
“…We therefore examined the potential for GDF9 to display either 1) autocrine actions on FSH synthesis and secretion by gonadotrophs in the manner of activin that is subject to antagonism by inhibin (Corrigan et al 1991, Li et al 1998 or 2) synergism with activin to stimulate FSH production in the manner of BMP (Lee et al 2007b, Nicol et al 2008. However, GDF9 (1-50 ng/ml) did not significantly increase FSH secretion (Fig.…”
Section: Lack Of Gdf9 Effects On Fsh Secretion By Rat and Mouse Gonadmentioning
confidence: 99%
“…We therefore examined the potential for GDF9 to display either 1) autocrine actions on FSH synthesis and secretion by gonadotrophs in the manner of activin that is subject to antagonism by inhibin (Corrigan et al 1991, Li et al 1998 or 2) synergism with activin to stimulate FSH production in the manner of BMP (Lee et al 2007b, Nicol et al 2008. However, GDF9 (1-50 ng/ml) did not significantly increase FSH secretion (Fig.…”
Section: Lack Of Gdf9 Effects On Fsh Secretion By Rat and Mouse Gonadmentioning
confidence: 99%
“…In addition to the negative regulation of gonadotropin production by PTGFRN, BMP signaling has also been shown to interfere with hormone production in pituitary gonadotrophs (42,43 Figure 4G). Moreover, testicular expression of the Leydig cell marker CYP17A1 was reduced by 35% ( Figure 4H).…”
Section: Mir-7 Targets Ptgfrn and Glg1 Regulate Expression And Secretmentioning
confidence: 99%
“…However, modulation of FSHB transcription by BMPs varies between species (Visser & Themmen 2014). In murine primary pituitary cells, various BMPs including BMP15, BMP7, BMP6, and BMP4 stimulate FSHB transcription (Huang et al 2001, Otsuka & Shimasaki 2002, Nicol et al 2008, whereas BMP6 and BMP4 inhibit FSHB transcription in ovine cells (Faure et al 2005). In accordance with the stimulatory effect of BMPs in murine primary pituitary cells, it has been shown that BMP2 acts synergistically with Activin A to regulate FSHb expression in LbT2 cells (Lee et al 2007, Wang et al 2014.…”
Section: Discussionmentioning
confidence: 92%